2017
DOI: 10.1371/journal.pone.0184837
|View full text |Cite
|
Sign up to set email alerts
|

Ocular biometric measurements in cataract surgery candidates in Portugal

Abstract: ObjectiveDescribe the ocular biometric parameters and their associations in a population of cataract surgery candidates.MethodsA cross-sectional study of 13,012 eyes of 6,506 patients was performed. Biometric parameters of the eyes were measured by optical low-coherence reflectometry. The axial length (AL), mean keratometry (K) and astigmatism, anterior chamber depth (ACD) (epithelium to lens), lens thickness (LT), and Corneal Diameter (CD) were evaluated.ResultsThe mean age was 69 ± 10 years (44–99 years). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
60
4
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 22 publications
12
60
4
4
Order By: Relevance
“…Similar to the present study Ferreira et al reported there was the positive association between AL, K and ACD (p>0.05) and CD, and the negative association between AL and LT. 12 These results are in concurrence with those presented in the literature except for K, whose association with AL is inverse in most series, showing emmetropic association between corneal curvature and AL. [26][27][28] Although there may be population differences and the correlation with refractive error has not been addressed in this study, the different published studies in the literature reported keratometry assessed with automatic, manual, or IOL master keratometry, and these values cannot be compared directly with ours because of different methods of measurement and refractive indices used.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar to the present study Ferreira et al reported there was the positive association between AL, K and ACD (p>0.05) and CD, and the negative association between AL and LT. 12 These results are in concurrence with those presented in the literature except for K, whose association with AL is inverse in most series, showing emmetropic association between corneal curvature and AL. [26][27][28] Although there may be population differences and the correlation with refractive error has not been addressed in this study, the different published studies in the literature reported keratometry assessed with automatic, manual, or IOL master keratometry, and these values cannot be compared directly with ours because of different methods of measurement and refractive indices used.…”
Section: Discussionsupporting
confidence: 92%
“…13 Age at the time of cataract operation varies from country to country example, in southern Chinese11 mean age was 70.4±10.5 years about 7 years older than our patients. The mean age 64.04±10.81 years was reported Natung et al 12 This implies that the cataract problem increases with age and it mainly occurs in 7th decade of life.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…It is insufficient to place a thick IOL with its principal plane at the ELP for ray-tracing simulations of the pseudophakic eye with a thick IOL. The difference between the ALP and ELP (IOL with P = 20 D) varies by less than 0.03 mm as a function of DC for the normal range of DC (between 40 D and 51 D [ 14 ]). The corneal power has larger impact for thick low powered IOLs.…”
Section: Discussionmentioning
confidence: 99%